Quinn’s leadership roles: a confirmatory factor analysis study in Portuguese health services - Parreira, P.; Lopes, A.; Salgueiro, M. F.; Carvalho, C.; Salgueiro-Oliveira, A.; Castilho, A.; Mónico, L.; Sena, C. A.; Fonseca, C. (Revista Ibero-Americana de Saúde e Envelhecimento, 2015)
Purpose: To assess the psychometric properties of Quinn’s leadership questionnaire (CFV questionnaire; 1988) in Portuguese health services. Design: Cross-sectional study, using Quinn’s leadership questionnaire, administered to registered nurses and physicians in Portuguese health services (N = 687). Method: Self-administered survey applied to two samples. In the first sample (convenience; N = 249 Portuguese health professionals), exploratory factor and reliability analyses were performed to the CFV questionnaire. In the second sample (stratified; N = 50 surgical units of 33 Portuguese hospitals), confirmatory factor analyses were performed using LISREL 8.80. Findings: In the first sample, an eight-factor solution emerged accounting for 65.46% of the total variance, in an interpretable factor structure (loadings> .50), with Cronbach’s ? greater than .79. This factor structure, replicated in the second sample, showed reasonable goodness-of-fit of the model to each of the leadership roles, that is, to the eight quadrants and global model. Overall, the models showed nomological validity, with scores between good and acceptable (.235 < x2/df < 2.055 and .00 < RMSEA < .077). Conclusions: Quinn’s leadership questionnaire showed good reliability and validity for the eight leadership roles, proving to be suitable for use in health care/hospital settings.